Tuberculosis in AIDS patients - Nissapatorn, V.; Lee, C.; Ithoi, I.; Fong, M.Y.; Abdullah, K.A. (2003)
Tuberculosis is the top agenda among opportunistic diseases and the most leading cause of death in HIV/AIDS patients. A total of 406 AIDS patients were recruited in this retrospective and descriptive study. 123/406 (30.3) were diagnosed as AIDS-related tuberculosis (TB). Their age range from 17 to 69 years with a mean (Â±SD) of 37.2 (Â±9.51. There were significant association between occupation, or mode of HIV transmission and tuberculosis infection (p< 0.05). Pulmonary tuberculosis 104/123 (84.6) was the most common disease location among TB patients. We found the significant association between the clinical presentations i.e. fever, cough, sputum or hemoptysis and TB patients (p<0.05), moreover, the level of CD4 cell count plays a significant role in association with the disease (p<0.05) in this study.